(3GdLZQGajG GdSjGMjI (B:s (3JWHjbGJ Ydi GdhWf GdYQHj (B/s - (3HXGXh, GHQGgje Ndjds ((3YeGf(B: s (3eDSSI GdhQGb(B, s, 2009)
(3GdJWhQ GdJGQjNj dUfGYI GdSjGMI , GdLZQdajG GdSjGMjI fXQI JMdjdjI h eYGdLI YdejI , GdNQGFW GdSjGMjI , LZQGajI GdhWf GdYQHj , GdebheGJ GdLZQGajI dUfGYI GdSjGMI aj GdhWf GdYQHj , JMdjd GJLGgGJ GdMQcI GdSjGMjI aj GdhWf GdYQHj , GdJhRjY GdLZQGaj dCTcGd GdSjGMI aj GdhWf GdYQHj , GSJNOGeGJ fXGe GdeYdheGJ GdLZQGaj (BGIS (3aj GdSjGMI , GdJhRjY GdLZQGaj dehGbY GdJQGK GdYGdej aj GdhWf GdYQHj h dehGbY YLGFH GdOfjG aj GdYGde , GdJQHjI GdSjGMjI aj GdhWf GdYQHj , GdGWGQ GdYGe ddESJQGJjLjI GdSjGMjI GdYQHjI , eSJbHd GdSjGMI aj GdhWf GdYQHj aj Xd GdJZjQGJ GdYGdejI GdeYGUQI , GdYdGbI Hjf GdGfSGf h GdSjGMI h GdHjFI , GdeMejGJ GdWHjYjI , GdJCKjQGJ GdLZQGajI Ydi UfGYI GdSjGMI , MGdGJ OQGSjI aj GdLZQGajG GdSjGMjI aj CbWGQ GdhWf GdYQHj (B.s
(3eQGLY U(B.593 (3; GTcGds
Keywords: (3GdGeGcf GdSjGMjIs; (3GdHdOGf GdYQHjIs; (3GdLZQGajG GdSjGMjIs; (3GdSjGMIs; (3GdhWf GdYQHjs; (3UfGYI GdSjGMIs